36+8x=5(5x-5)-7

Simple and best practice solution for 36+8x=5(5x-5)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36+8x=5(5x-5)-7 equation:


Simplifying
36 + 8x = 5(5x + -5) + -7

Reorder the terms:
36 + 8x = 5(-5 + 5x) + -7
36 + 8x = (-5 * 5 + 5x * 5) + -7
36 + 8x = (-25 + 25x) + -7

Reorder the terms:
36 + 8x = -25 + -7 + 25x

Combine like terms: -25 + -7 = -32
36 + 8x = -32 + 25x

Solving
36 + 8x = -32 + 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
36 + 8x + -25x = -32 + 25x + -25x

Combine like terms: 8x + -25x = -17x
36 + -17x = -32 + 25x + -25x

Combine like terms: 25x + -25x = 0
36 + -17x = -32 + 0
36 + -17x = -32

Add '-36' to each side of the equation.
36 + -36 + -17x = -32 + -36

Combine like terms: 36 + -36 = 0
0 + -17x = -32 + -36
-17x = -32 + -36

Combine like terms: -32 + -36 = -68
-17x = -68

Divide each side by '-17'.
x = 4

Simplifying
x = 4

See similar equations:

| y/3=69 | | 8x+2(-5x-4)=-12 | | w/2=44 | | 360=16x-4+16x-4+14x+34+14x+34 | | 12x+9=75 | | -120=-12x | | 5x-12.3=2x+9 | | 105=8p+9 | | a^2+18a+40=-5 | | 36-7p=-7(p-5) | | m+m-24+m+15=99 | | 57=9s+3 | | 5s+7-2x=40 | | 4x+4=7*8 | | x^-4=1/4096 | | A(t)=900(0.85)t | | -4-2y=2x | | 7p+7=63 | | x^-2=1/36 | | 6.1=-4+x | | k+2=9*18 | | 2x+(x+3)=38 | | Y=(-1/3)1.3-6 | | -(x+8)=-35+8x | | y=2xSqrt[1-x^2] | | 7(2+5v)=3v+14 | | 88/ | | xy(x+y)=0 | | x(x+3)=6x+45 | | 12x^2-22x-14=0 | | 6-6k=-6 | | 2f(t)=x^2+6 |

Equations solver categories